Impact of Vitamin C on Gene Expression Profile of Inflammatory and Anti-Inflammatory Cytokines in the Male Partners of Couples with Recurrent Pregnancy Loss - Farzaneh Fesahat; Efat Norouzi; Seyed Mohammad Seifati; Saeideh Hamidian; Akram Hosseini; Fateme Zare (International Journal of Inflammation)
Immune system disorders and increased inflammation in the male reproductive system can lead to fetal risk in the early stages of development and implantation. Antioxidants such as vitamin C can play a protective role against sperm inflammatory reactions. This study aimed to evaluate the effect of vitamin C on the expression of inflammatory and anti-inflammatory cytokine genes in the male partners of couples with recurrent pregnancy loss. In this randomized clinical trial, twenty male partners of couples with RPL were examined for sperm parameters and expression profile of some inflammatory and anti-inflammatory cytokine genes before and after treatment with vitamin C. There was a statistically significant higher rate of normal morphology and sperm concentration in each patient before and after treatment with vitamin C p≤0.05. The mRNA levels of interleukin 6 and tumor necrosis factor-alpha were significantly decreased in the sperm of patients after treatment with vitamin C compared to before treatment. In contrast, the gene expression levels of interleukin 4 and transforming growth factor-beta showed a significant increase in the sperm of patients after treatment with vitamin C. Oral daily administration of vitamin C may be effective in the fertility potential of male partners of couples with RPL not only through the improvement of the sperm parameters but also by modulating the expression profile of inflammatory and anti-inflammatory genes. Further studies on protein levels are needed to clarify the role of TNF-⍺ and IFN-γ as a prognostic value in evaluating the recurrent abortion risk in infertile male partners. This trial is registered with IRCT20180312039059N1.